Social Capital in Community Development at Prone Disaster Area: A Lesson Learnt at Sempu Village, Nglancar, Kediri, East Java, Indonesia - Windiani Windiani; Arfan Fahmi; Zainul Muhibbin (IPTEK Journal of Proceedings Series, 2019)
This study aims to analyze the role of social capital in community development in disaster prone areas. The study was conducted in a disaster-prone area of Mount Kelud, Sempu Village, Ngancar District, Kediri Regency after the eruption in 2014. The study used a qualitative method with an ethnographic approach. The results showed that after the eruption in 2014, social capital in the community became a source of strength in community development in the Mount Kelud disaster-prone areas, especially in the process of restoring the social and economic life of the Sempu village community. Social ties, trusts, social networks that are strongly intertwined are the elements of social capital that are still strong which are found in the study area. The results of the study also found a responsive, innovative and transparent leadership pattern developed by the Village Head helped accelerate the recovery process of the socio-economic life of the Sempu village community. The results of the study also revealed that the social capital owned by the local community was tested for strength when dealing with external forces such as the presence of institutions and volunteers involved in the recovery process. This situation triggered tensions between residents and the apparatus assigned to distribute aid.